2001
DOI: 10.1016/s0735-1097(01)01651-5
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive single-beat determination of left ventricular end-systolic elastance in humans

Abstract: The E(es) can be reliably estimated from simple noninvasive measurements. This approach should broaden the clinical applicability of this useful parameter for assessing systolic function, therapeutic response and ventricular-arterial interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
488
1
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 534 publications
(520 citation statements)
references
References 24 publications
10
488
1
10
Order By: Relevance
“…Briefly, single‐beat LV elastance (E es(sb) ) was calculated by:normalEes(sb)=false[Pd(normalEnd(est)×LVESP)false]/false[SV×Enormalndfalse(normalestfalse)false]where E nd(est) is the time and amplitude normalized estimated time varying elastance, P d is central aortic diastolic pressure, LVESP is the LV end‐systolic pressure, and SV is stroke volume. The E nd(est) was estimated form a regression model based on invasive PV data using a 7‐term polynomial function, LVEF, central aortic end‐systolic and diastolic pressures, and the ratio of pre‐ejection period to total systolic period, as described elsewhere 15. E a was estimated by dividing end‐systolic pressure to stroke volume.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, single‐beat LV elastance (E es(sb) ) was calculated by:normalEes(sb)=false[Pd(normalEnd(est)×LVESP)false]/false[SV×Enormalndfalse(normalestfalse)false]where E nd(est) is the time and amplitude normalized estimated time varying elastance, P d is central aortic diastolic pressure, LVESP is the LV end‐systolic pressure, and SV is stroke volume. The E nd(est) was estimated form a regression model based on invasive PV data using a 7‐term polynomial function, LVEF, central aortic end‐systolic and diastolic pressures, and the ratio of pre‐ejection period to total systolic period, as described elsewhere 15. E a was estimated by dividing end‐systolic pressure to stroke volume.…”
Section: Methodsmentioning
confidence: 99%
“…A more powerful and largely load‐independent measure of contractile function is LV end‐systolic elastance (E es ), which can be defined as the stiffness of the left ventricle at the end of the systole. The arterial system can also be assessed in elastance terms; hence, ventricular‐arterial coupling (VAC) can be expressed by the comparison of ventricular and arterial elastances (E a ) 12, 13, 14, 15. Experimental models showed that LV EW is maximal when the VAC (E es /E a ) ratio is 1,12 whereas the mechanical efficiency is maximal when the ratio is 2 13, 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of arterialvascular interaction were made in accordance with previously validated methodologies. 11,12 To calculate effective EaI we calculated effective Ea from stroke volume (by 3D echocardiography) and systolic BP and adjusted by body area. Ees was calculated using systolic and diastolic BP, stroke volume, preejection and total-systolic times.…”
Section: Echocardiographymentioning
confidence: 99%
“…This echocardiographic approach has been validated by direct comparisons with invasive analysis of pressure-volume curves. 11,12 The non-invasive nature of the method makes it suitable for clinical use and for monitoring of treatment effectiveness, leading to its growing popularity among researchers.…”
Section: Vascular Ventricular Coupling In Malignant Hypertensionmentioning
confidence: 99%